Studying the NAIRU and its implications - Vasiliki Bozani; Nick Drydakis (Institute for the Study of Labor (IZA), 2011)
The current paper is a means of demonstrating our knowledge about macroeconomic theories, and its key variables, phenomena, and history. Given the key role that the Non-Accelerating Inflation Rate of Unemployment (NAIRU) has in the macroeconomic theory as well as its role in determining employment theories, it is raised the need for a thorough evaluation of its origins and a brief explanation of some of the claims surrounding it. In these grounds, this study aims at integrating and generalizing findings and presenting the changes within the macroeconomic field over the years by investigating theories, identifying methodological strengths and the weaknesses in the body of the macroeconomic research about the concept of NAIRU. In order to help the reader to avoid misunderstandings we define the best descriptors and identify the best sources to use in the review literature related to our topic, we rely on primary sources in reviewing the literature, we examine critically all aspects of the research design and analysis, and we consider contrary findings and alternative interpretations in synthesizing quantitative literature.
urn:nbn:de:101:1-201111212943
Keywords: E02; E24; E61; 330; NAIRU; macroeconomic policies; Natürliche Arbeitslosigkeit; Makroökonomik